2018
DOI: 10.1021/acschemneuro.8b00142
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of Arylamide Phenylpiperazine Ligands To Investigate the Factors Influencing D3 Dopamine Receptor Bitropic Binding and Receptor Subtype Selectivity

Abstract: We have previously reported on the ability of arylamide phenylpiperazines to bind selectively to the D3 versus the D2 dopamine receptor subtype. For these studies, we used LS-3-134 as the prototypic arylamide phenylpiperazine ligand because it binds with high affinity at D3 dopamine receptor (0.17 nM) and exhibits >150-fold D3 vs D2 receptor binding selectivity. Our goal was to investigate how the composition and size of the nonaromatic ring structure at the piperazine position of substituted phenylpiperazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 72 publications
1
40
0
Order By: Relevance
“…Calculation of their respective binding energies using MM-PBSA showed that the strength of the electrostatic interaction with the D 3.32 residue generally decreased as the size of the piperazine substituent increased. Umbrella sampling simulations were used to generate a PMF aimed at mimicking the unbinding of the ligand protonated nitrogen from the D 3.32 residue, and the depth of the bound state in the PMF also agreed with the experimental trend except for one of the analogs (Hayatshahi et al, 2018).…”
Section: Dopamine Receptorsmentioning
confidence: 82%
See 2 more Smart Citations
“…Calculation of their respective binding energies using MM-PBSA showed that the strength of the electrostatic interaction with the D 3.32 residue generally decreased as the size of the piperazine substituent increased. Umbrella sampling simulations were used to generate a PMF aimed at mimicking the unbinding of the ligand protonated nitrogen from the D 3.32 residue, and the depth of the bound state in the PMF also agreed with the experimental trend except for one of the analogs (Hayatshahi et al, 2018).…”
Section: Dopamine Receptorsmentioning
confidence: 82%
“…Another recent joint experimental-computational publication also made use of MD simulations to help explain the molecular basis for the binding of bitopic arylamide phenylpiperazine ligands selective for the D3 receptor over D2 (Hayatshahi et al, 2018). Specifically, studies were focused on the prototypic arylamide phenylpiperazine LS-3-134 ligand, which has been found to act as a D3 receptor partial agonist and has also been shown to be 150-fold more selective for the D3 receptor relative to the D2 receptor (Tu et al, 2011).…”
Section: Dopamine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the orthosteric binding site of D2-like dopamine receptors is constructed by conserved amino acid residues in the transmembrane helical spanning regions, it is not surprising that many of the original D2 vs. D1 selective ligands bind nonselectively at the D2 and D3 dopamine receptor subtypes. Ligands that can simultaneously interact with two different regions (an orthosteric and secondary binding site (SBS) on a single GPCR have been described as bitopic ligands [ 20 , 21 , 22 , 23 , 24 ]. The ability of some N -phenylpiperazine benzamides to bind selectively at the D3 dopamine receptor subtype has been attributed to the ability of the N -phenylpiperazine moiety to occupy either the D2 or D3 dopamine orthosteric binding site, while the benzamide moiety interacts with an SBS that is unique to the D3 dopamine receptor subtype [ 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ligands that can simultaneously interact with two different regions (an orthosteric and secondary binding site (SBS) on a single GPCR have been described as bitopic ligands [ 20 , 21 , 22 , 23 , 24 ]. The ability of some N -phenylpiperazine benzamides to bind selectively at the D3 dopamine receptor subtype has been attributed to the ability of the N -phenylpiperazine moiety to occupy either the D2 or D3 dopamine orthosteric binding site, while the benzamide moiety interacts with an SBS that is unique to the D3 dopamine receptor subtype [ 21 , 24 ]. Consequently, a number of research groups have been able to develop D3 vs. D2 dopamine receptor selective ligands using a substituted N -phenylpiperazine benzamide template to identify ligands that bind selectively and with high affinity at the D3 dopamine receptor subtype [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%